High School Agricultural Communication Competencies: A National Delphi - Mackenzie Atkins; Ricky Telg; Kati Lawson; Lauri M. Baker (Journal of Applied Communications, 2025)
This national study aimed to establish a current consensus on the competencies required for high school students completing agricultural communication courses. Additionally, the study identified the ideal introductory level for each competency. It offers an updated overview of the key agricultural communication competencies for high school students. The results of this study build on previous studies identifying competencies needed for high school agricultural communication courses. This study was conducted through a two-round Delphi study, in which the panel of experts consisted of high school agriculture educators who teach agricultural communication courses from across the United States. The researcher found an additional six agricultural communication competencies needed in high school agricultural education. The results showed that three competencies (pre-identified) did not reach the level of agreement necessary to be considered important in a high school agricultural communications curriculum. The researchers suggest that these findings should be considered when creating a standardized curriculum for high school agricultural communication courses.
Keywords: Agricultural communication(s); high school; competencies; agriculture education; Delphi